Anatomy of the spinal dorsal root entry zone: its clinical significance - ZİYAL, MUSTAFA İBRAHİM; KİRAZLI, ÖZLEM (SPRINGER WIEN, 2014)
The posterolateral sulcus (PLS) is an important surgical landmark, especially for DREZ (dorsal root entry zone) operations. The present study aimed to show the variations of the PLS using human spinal cord histological sections and report the variability in the number of dorsal rootlets of the spinal nerves in each the spinal cord segment. Further, measure the height and width of the dorsal horn on histological sections for cervical, thoracic, and lumbar levels. The results of the present study showed various patterns of PLS 1.clearly present PLS, 2. short PLS, 3. absent PLS or 4. irregular PLS. Height and width measurements of the dorsal horn showed that the average width was greatest at lower cervical (0.48 +/- 0.04 mm) and least at lower thoracic levels (0.41 +/- 0.04 mm), whereas the average height was greatest at upper cervical (3.0 +/- 0.06 mm) and smallest at lower lumbar levels (1.8 +/- 0.08 mm). The average number of rootlets varied considerably, at cervical level it was 7.6 +/- 1.4 mm, at thoracic 6.6 +/- 0.8 mm and at lumbar 6.1 +/- 0.4 mm. The detailed anatomy of the variations of the PLS and the average number of rootlets at each spinal level can increase the success of regional surgery. Further, fine measurements on histological sections can give detailed knowledge on the size necessary for lesioning in DREZ operations.
Keywords: DREZ; Posterolateral sulcus; Variations; Spinal cord; Dorsal root; Measurement; MICROSURGICAL ANATOMY; BRACHIAL-PLEXUS; PAIN RELIEF; LESIONS; CORD; HORN; MICROELECTRODE; EXPERIENCE; OPERATIONS; RECORDINGS